Bioactivated Glucoraphanin Modulates Genes Involved in Necroptosis on Motor-Neuron-like Nsc-34: A Transcriptomic Study - Aurelio Minuti; Alessandra Trainito; Agnese Gugliandolo; Ivan Anchesi; Luigi Chiricosta; Renato Iori; Emanuela Mazzon; Marco Calabrò (MDPI AG, 2024)
Research on bioactive compounds has grown recently due to their health benefits and limited adverse effects, particularly in reducing the risk of chronic diseases, including neurodegenerative conditions. According to these observations, this study investigates the activity of sulforaphane (RS-GRA) on an in vitro model of differentiated NSC-34 cells. We performed a transcriptomic analysis at various time points (24 h, 48 h, and 72 h) and RS-GRA concentrations (1 µM, 5 µM, and 10 µM) to identify molecular pathways influenced by this compound and the effects of dosage and prolonged exposure. We found 39 differentially expressed genes consistently up- or downregulated across all conditions. Notably, Nfe2l2, Slc1a5, Slc7a11, Slc6a9, Slc6a5, Sod1, and Sod2 genes were consistently upregulated, while Ripk1, Glul, Ripk3, and Mlkl genes were downregulated. Pathway perturbation analysis showed that the overall dysregulation of these genes results in a significant increase in redox pathway activity (adjusted p-value 1.11 × 10−3) and a significant inhibition of the necroptosis pathway (adjusted p-value 4.64 × 10−3). These findings suggest RS-GRA's potential as an adjuvant in neurodegenerative disease treatment, as both increased redox activity and necroptosis inhibition may be beneficial in this context. Furthermore, our data suggest two possible administration strategies, namely an acute approach with higher dosages and a chronic approach with lower dosages.